Sains modern dalam prespektif Islam - Wahidah, Shofiyah Risalatul (Maliki Interdisciplinary Journal, 2023)
The development of modern science today creates many new innovations. Science makes it easy for us to do our daily activities. But in addition to science it also has a big negative impact. This study aims to find out how modern science is in an Islamic perspective along with examples, positive and negative impacts. The data used is from books and journals that are spread in the media. The results of this study indicate that Islam has its own perspective regarding science contained in the Koran. Contrary to Islamism's view of science, there is no contradiction between Islam and modern science. In Islamic science, the Qur'an and nature are sources of science and spiritual knowledge that provide scientific principles that are always related to metaphysical and spiritual knowledge.